2022
DOI: 10.3389/fendo.2022.1022752
|View full text |Cite
|
Sign up to set email alerts
|

Body composition in children and adolescents with non-classic congenital adrenal hyperplasia and the risk for components of metabolic syndrome: An observational study

Abstract: BackgroundTreated or untreated non-classic congenital adrenal hyperplasia (NCCAH) diagnosed in childhood could pose an increased risk of obesity and metabolic derangements in adolescence and early adulthood. We aimed to explore the interaction between muscle-to-fat ratio (MFR) and components of metabolic syndrome in pediatric subjects with NCCAH.MethodsThis retrospective observational study was conducted in the Tel Aviv Medical Center from January 2018 to January 2022. The study group comprised 75 subjects (26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Recently, Delai et al reported that insulin resistance was present in adolescent/young adult patients with NC-CAH (25 females, 6 males) investigated by insulin-euglycemic clamp and it was related to prolonged use and long-acting glucorticoid treatment [26]. Ben Simon et al [27], by studying 75 subjects (49 females) with NC-CAH (61 hydrocortisone-treated and 14 untreated) as well as 134 healthy sex-and age-matched controls, reported that children and adolescents with NC-CAH have a body composition characterized by an imbalance between muscle and fat tissues, which may place them at increased risk for early-onset cardio-metabolic derangements. Glucocorticoid therapy did not appear to adversely affect their body composition [27].…”
Section: Clinical Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Delai et al reported that insulin resistance was present in adolescent/young adult patients with NC-CAH (25 females, 6 males) investigated by insulin-euglycemic clamp and it was related to prolonged use and long-acting glucorticoid treatment [26]. Ben Simon et al [27], by studying 75 subjects (49 females) with NC-CAH (61 hydrocortisone-treated and 14 untreated) as well as 134 healthy sex-and age-matched controls, reported that children and adolescents with NC-CAH have a body composition characterized by an imbalance between muscle and fat tissues, which may place them at increased risk for early-onset cardio-metabolic derangements. Glucocorticoid therapy did not appear to adversely affect their body composition [27].…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Ben Simon et al [27], by studying 75 subjects (49 females) with NC-CAH (61 hydrocortisone-treated and 14 untreated) as well as 134 healthy sex-and age-matched controls, reported that children and adolescents with NC-CAH have a body composition characterized by an imbalance between muscle and fat tissues, which may place them at increased risk for early-onset cardio-metabolic derangements. Glucocorticoid therapy did not appear to adversely affect their body composition [27]. Albeit, long-term prospective studies should be warranted to better assess these issues in NC-CAH, it seems appropriate to recommend periodic metabolic follow-up, healthy lifestyle indications in both treated and untreated children to prevent the long-term risk of obesity, hypertension and abnormal body composition [6,13].…”
Section: Clinical Findingsmentioning
confidence: 99%